Morphometric Changes in Lung Tissue During Chemical Burn of the Digestive Tract (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Lung pathology is quite widespread and has been studied in detail by both clinicians and morphologists. But morphometric changes in lung tissue during a chemical burn of the digestive tract have been poorly studied and require further research. In case of a chemical burn of the digestive tract with acetic acid, such morphological changes were revealed as pulmonary edema, a decrease in the volume fraction of the alveoli, destroyed epithelial cells and red blood cells were detected in the lumen of the alveoli, thickening of the interalveolar septa and an increase in their volume fraction were noted, which is associated with dystrophic changes in the alveolocytes and endothelium of the blood vessels. blood vessels and swelling of the interstitial tissue of the alveoli. As a result of developed edema and destructive changes, the relative volume of collagen and reticular fibers in the lung stroma decreases. A slight leukocyte infiltration is detected paravasally.